Industry Workforce Development: The Value of Internships. Issue 7 (1st September 2022) - Adams, Hunter; Reeder, Sam; Appleton, Emily; Thomas, Dave; Southard, Mark
Key Takeaways: As its current workforce ages and retires, the water industry needs to bring in ambitious, young employees to keep the water flowing. Classrooms provide students with technical knowledge, and internships provide them with hands‐on experience that will help them stand out in job applications. Internships allow employers to see how prospective applicants work under pressure to determine if they are a good fit for the team. Internship programs provide a potential pipeline for new employees who may have not otherwise known about water industry positions.